Perlindungan Hukum Terhadap Perempuan Dan Anak Korban Kekerasan Seksual - Fatimatul Risna; Asep Suherman (CV. ITTC INDONESIA, 2024)
As time goes on, the conditions and lifestyle of children deteriorate because, as far as they can tell, the world and society are causing problems for children. In 2021, 8.43% of children and adults reported sexual dysfunction, and by 2024, that number had risen to 8.82%. This research aims to analyze, describe, and illustrate the legal protections afforded to parents and children who become victims of sexual abuse and other forms of violence. This type of research is normative, employing conceptual frameworks and principles. The results of this study indicate that legal protection against women and children who are victims of sexual violence is regulated in the 1945 Constitution, Criminal Code, Law 39/1999, Law 35/2014, Law 11/2012, Perppu 17/2016, Law 12/2022, Law 23/2004, Law 16/2011, Law 13/2006, Law 26/2000 and in the implementation of legal protection against women and children who are victims of sexual violence there are several obstacles faced, these obstacles come from law enforcement factors that do not carry out their obligations according to existing regulations, lack of facilities for victims, factors from the victims themselves who have a fear of reporting, and lack of attention from the community.